Differential Regulation of Short- and Long-Tract Gene Conversion between Sister Chromatids by Rad51C - Nagaraju, Ganesh (American Society for Microbiology, 2006)
The Rad51 paralog Rad51C has been implicated in the control of homologous recombination. To study the role of Rad51C in vivo in mammalian cells, we analyzed short-tract and long-tract gene conversion between sister chromatids in hamster Rad51C(−/−) CL-V4B cells in response to a site-specific chromosomal double-strand break. Gene conversion was inefficient in these cells and was specifically restored by expression of wild-type Rad51C. Surprisingly, gene conversions in CL-V4B cells were biased in favor of long-tract gene conversion, in comparison to controls expressing wild-type Rad51C. These long-tract events were not associated with crossing over between sister chromatids. Analysis of gene conversion tract lengths in CL-V4B cells lacking Rad51C revealed a bimodal frequency distribution, with almost all gene conversions being either less than 1 kb or greater than 3.2 kb in length. These results indicate that Rad51C plays a pivotal role in determining the “choice” between short- and long-tract gene conversion and in suppressing gene amplifications associated with sister chromatid recombination.